2010
DOI: 10.1007/s11033-010-0539-7
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of the interaction between ribavirin and bovine serum albumin by spectroscopic methods

Abstract: The interaction between ribavirin (RIB) with bovine serum albumin (BSA) has been investigated by fluorescence quenching technique in combination with UV-vis absorption and circular dichroism (CD) spectroscopies under the simulative physiological conditions. The quenching of BSA fluorescence by RIB was found to be a result of the formation of RIB-BSA complex. The binding constants and the number of binding sites were calculated at three different temperatures. The values of thermodynamic parameters ∆H, ∆S, ∆G a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In Fig. 6(A, b, B, b), the maximum emission wavelength of Trp residues did not have a significant shift in the presence of ergosterol, suggesting that the microenvironments around Trp residues had no discernable change during the interaction of ergosterol with BSA/HSA [28]. However, it could be seen from Fig.…”
Section: Conformational Investigationsmentioning
confidence: 86%
See 2 more Smart Citations
“…In Fig. 6(A, b, B, b), the maximum emission wavelength of Trp residues did not have a significant shift in the presence of ergosterol, suggesting that the microenvironments around Trp residues had no discernable change during the interaction of ergosterol with BSA/HSA [28]. However, it could be seen from Fig.…”
Section: Conformational Investigationsmentioning
confidence: 86%
“…However, it could be seen from Fig. 7 that the strong fluorescence quenching of Trp residues decreased 57.2/58.6 % in fluorescence intensities of BSA/ HSA with the addition of ergosterol, indicating that ergosterol reached subdomain IIA, where the only one Trp residue (Trp-212/Trp-214) on BSA/HSA was located [28,30]. There was a large hydrophobic cavity in subdomain IIA which many drugs could bind to them.…”
Section: Conformational Investigationsmentioning
confidence: 91%
See 1 more Smart Citation
“…In Fig.8(A,b and B, b), the maximum emission wavelength of Trp residues did not have a significant shift in the presence of scopoletin, which suggested that the microenvironment around Trp residues had no discernable change during the interaction of scopoletin with BSA/ HSA [38]. However, It could be seen from Fig.…”
Section: Synchronous Fluorescence Spectroscopy Studiesmentioning
confidence: 86%
“…The shift in maximum emission wavelength reflects the change of the polarity around chromophore molecule. When Dl is stabilized at 15 and 60 nm, the synchronous fluorescence offers the characteristics of Tyr and Trp residues, respectively [38]. The fluorescence spectra of Tyr and Trp residues on BSA/HSA at various concentrations of scopoletin were shown in Fig.…”
Section: Synchronous Fluorescence Spectroscopy Studiesmentioning
confidence: 99%